1987
DOI: 10.1523/jneurosci.07-09-02927.1987
|View full text |Cite
|
Sign up to set email alerts
|

Selective D1 and D2 dopamine agonists differentially alter basal ganglia glucose utilization in rats with unilateral 6-hydroxydopamine substantia nigra lesions

Abstract: he relative roles of D1 and D2 dopamine receptor stimulation in mediating the antiparkinsonian effects of dopaminergic drugs remain unclear. To determine the functional metabolic consequences of selective dopamine receptor stimulation, we used 2-deoxyglucose (2-DG) autoradiography to examine the effects of the D1 agonist SKF-38393 and the D2 agonist LY-171555 on regional cerebral glucose utilization (RCGU) in rats with unilateral 6-hydroxydopamine (6-OHDA) substantia nigra lesions. SKF-38393 (0.5-25.0 mg/kg) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(56 citation statements)
references
References 26 publications
10
45
1
Order By: Relevance
“…In normal rats, D2 family agonists increase BOLD in brain regions enriched in D3 receptors, like the nucleus accumbens, but have little if any effect in dorsal striatum and motor cortex (Ireland et al, 2005). Our present findings showing that quinpirole does not induce BOLD changes in 6-OHDA-lesioned rats are consistent with previous studies establishing that D2 family agonists do not increase 2-deoxyglucose uptake and immediate early gene expression in the striatum of parkinsonian rats (Trugman and Wooten, 1987;Robertson et al, 1989;Paul et al, 1992;LaHoste et al, 1993). Contrasting with this lack of neuronal activation in the striatum, quinpirole induces mild AIMs and strong turning behavior in 6-OHDA-lesioned rats, which were sensitized to dopamine agonists (present findings and Delfino et al, 2004; see also Robertson et al, 1989;Paul et al, 1992).…”
Section: D1/d5 Dopamine Receptor Agonists Are More Powerful Inductorssupporting
confidence: 92%
See 1 more Smart Citation
“…In normal rats, D2 family agonists increase BOLD in brain regions enriched in D3 receptors, like the nucleus accumbens, but have little if any effect in dorsal striatum and motor cortex (Ireland et al, 2005). Our present findings showing that quinpirole does not induce BOLD changes in 6-OHDA-lesioned rats are consistent with previous studies establishing that D2 family agonists do not increase 2-deoxyglucose uptake and immediate early gene expression in the striatum of parkinsonian rats (Trugman and Wooten, 1987;Robertson et al, 1989;Paul et al, 1992;LaHoste et al, 1993). Contrasting with this lack of neuronal activation in the striatum, quinpirole induces mild AIMs and strong turning behavior in 6-OHDA-lesioned rats, which were sensitized to dopamine agonists (present findings and Delfino et al, 2004; see also Robertson et al, 1989;Paul et al, 1992).…”
Section: D1/d5 Dopamine Receptor Agonists Are More Powerful Inductorssupporting
confidence: 92%
“…On the other hand, the D1/D5 agonist SKF-81297 induced a strong striatal and cortical bilateral activation, which was higher in rats repeatedly exposed to the same agonist before MRI examination, and which was significantly higher than that induced by apomorphine. Early studies of 2-deoxyglucose uptake and immediate early gene expression recognized a powerful stimulatory effect of D1/D5 agonists in parkinsonian rats (Trugman and Wooten, 1987;Robertson et al, 1989;Paul et al, 1992;LaHoste et al, 1993). More recent work emphasized the bilateral effects of D1/D5 agonists on gene expression in the parkinsonian rat brain (Keefe and Gerfen, 1995;Blandini et al, 2003;Taymans et al, 2005) and demonstrated that direct stimulation of D1/D5 receptors in the denervated striatum can activate the motor cortex bilaterally (Keefe and Gerfen, 1995;Blandini et al, 2003).…”
Section: D1/d5 Dopamine Receptor Agonists Are More Powerful Inductorsmentioning
confidence: 99%
“…Moreover, the excitatory effects of the D1 receptor agonist seemed to be enhanced in the lesioned rat because a dose of SK F 38393 that did not significantly alter the firing of STN neurons in the intact rat significantly increased the firing in the lesioned rat. Augmentation of responses to D1 receptor agonists in the STN of the lesioned rat have been reported previously in studies measuring biochemical indexes of neuronal activation such as c-fos expression (Ruskin and Marshall, 1995) and glucose metabolism (Trugman and Wooten, 1987). One aspect of the D1 receptor-mediated effect in the STN that was altered by lesion was the role of the dopamine D2 receptor.…”
Section: Discussionsupporting
confidence: 58%
“…Dopamine D1 receptor stimulation was found to enhance the expression of c-fos in the STN of 6-hydroxydopamine-lesioned rats (Ruskin and Marshall, 1995), suggesting that the activity of STN neurons was increased. 2-Deoxyglucose uptake in the subthala-mus of dopamine-depleted monkeys (Mitchell et al, 1992) and rats (Trugman and Wooten, 1987;Engber et al, 1990) was also found to be increased after administration of dopamine receptor agonists; however, the interpretation of this result is unclear because it could reflect increased metabolism in inhibitory and/or excitatory afferents. Another study reported that the variability in response among STN neurons to the dopamine receptor antagonist haloperidol was increased in lesioned rats (Hollerman and Grace, 1992).…”
Section: Analysis; Firing Patternmentioning
confidence: 99%
“…The regional cerebral metabolic rate for glucose, rCMR glc , thought to represent energy consumed following depolarization of fine pre-synaptic axonal terminals (Sokoloff, 1999), is elevated in ipsilateral more than contralateral globus pallidus, lateral habenula, parafascicular and subthalamic nuclei and superior colliculus in 6-OHDA lesioned rats administered quinpirole (Morelli et al, 1993;Trugman & Wooten, 1987), as were our k* responses (Table 2). D-amphetamine increased rCMR glc less on the lesioned than intact side in one study (Wooten & Collins, 1983), as we found with our k* responses, but results in other studies involving rCMR glc are inconsistent (Palacios & Wiederhold, 1985;Trugman & Wooten, 1987).…”
Section: Discussionmentioning
confidence: 63%